High‐Resolution 3D Printing of Mechanically Tough Hydrogels Prepared by Thermo‐Responsive Poloxamer Ink Platform. Issue 2 (9th November 2021) - Imani, Kusuma Betha Cahaya; Jo, Ara; Choi, Gyeong Min; Kim, Beogyeong; Chung, Jin‐Woong; Lee, Heon Sang; Yoon, Jinhwan
Abstract: High‐resolution 3D‐printable hydrogels with high mechanical strength and biocompatibility are in great demand because of their potential applications in numerous fields. In this study, a material system comprising Pluronic F‐127 dimethacrylate (FDMA) is developed to function as a direct ink writing (DIW) hydrogel for 3D printing. FDMA is a triblock copolymer that transforms into micelles at elevated temperatures. The transformation increases the viscosity of FDMA and preserves its structure during DIW 3D printing, whereupon the printed structure is solidified through photopolymerization. Because of this viscosity shift, various functionalities can be incorporated through the addition of other materials in the solution state. Acrylic acid is incorporated into the pregel solution to enhance the mechanical strength, because the carboxylate group of poly(acrylic acid) ionically crosslinks with Fe 3+, increasing the toughness of the DIW hydrogel 37 times to 2.46 MJ m −3 . Tough conductive hydrogels are also 3D printed by homogenizing poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate into the pregel solution. Furthermore, the FDMA platform developed herein uses DIW, which facilitates multicartridges 3D printing, and because all the materials included are biocompatible, the platform may be used to fabricate complex structures for biological applications. Abstract : In this work, Pluronic F‐127 dimethacrylate is evaluated as a platform for extrusion hydrogel 3D printing. The platform can be incorporated with additional materials to achieve specific functionalities such as enhanced mechanical strength and conductivity. The platform is also biocompatible, which makes it promising for the fabrication of complex structures for biological applications by 3D printing.